Metodyczne aspekty wybranych sposobów zarządzania kapitałem intelektualnym - Jasińska, Agnieszka (Methodical aspects of chosen methods of intellectual capital management, 2006)
The author of the article points to the importance of Intellectual Capital for the competitiveness of the enterprise. The author mentions that there are a lot of different methods of Intellectual Capital Management but till now none of them is perfect. In this article the author presents them closer and compares two of them: the Balanced Scorecard and Skandia Navigator.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (4); 2006; nr 1114, s. 101-109